2021
DOI: 10.1038/s41598-021-81977-z
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation efficacy of atmospheric air plasma and airborne acoustic ultrasound against bacterial biofilms

Abstract: Biofilms are complex microbial communities that present serious contamination risks to our environment and health. In this study, atmospheric air plasma and airborne acoustic ultrasound technology were applied to inactivate Escherichia coli and Listeria innocua biofilms. Both technologies were efficient in controlling, or completely inactivating, the target bacterial biofilms. Viability and metabolic assays, along with microscopy analysis, revealed that atmospheric air plasma and airborne acoustic ultrasound d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…EM is a drug with significant anti-inflammatory and antibacterial activity (37,38), thus it has potential to replace antibiotics as an effective drug for treating acute osteomyelitis. Previous studies have reported the antibacterial effect of ultrasound in food packaging (39), and LFLIU has also been reported to stimulate ROS production, which provides a specific repressive effect on the growth of suspended bacteria and bacterial biofilms (12,13,40). In this study, it found that M-LFLIU combined with EM had significant synergistic antibacterial effects in vitro and in vivo, providing a promising possibility for alternative clinical treatments of acute osteomyelitis.…”
Section: Discussionmentioning
confidence: 50%
“…EM is a drug with significant anti-inflammatory and antibacterial activity (37,38), thus it has potential to replace antibiotics as an effective drug for treating acute osteomyelitis. Previous studies have reported the antibacterial effect of ultrasound in food packaging (39), and LFLIU has also been reported to stimulate ROS production, which provides a specific repressive effect on the growth of suspended bacteria and bacterial biofilms (12,13,40). In this study, it found that M-LFLIU combined with EM had significant synergistic antibacterial effects in vitro and in vivo, providing a promising possibility for alternative clinical treatments of acute osteomyelitis.…”
Section: Discussionmentioning
confidence: 50%
“…However, as PAW is yet a novel technology, a detailed investigation of its mechanism of action and potential interactions with EPS matrix and other biofilm compounds is yet to be performed. It is well known that biofilm maturity significantly affects plasma penetration because thicker biofilms with more biomass provide a better protection against reactive species (Chen et al, 2017; Hathaway et al, 2019; Patange et al, 2021). The same effect was observed in the current study, when the 72 h mature biofilms were found to be most resistant against PAW treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PAW is considered a promising technology, showing apparent suitability to substitute more traditional treatments used in a wide range of sectors, for example chlorine‐based (Patange et al, 2021; Xiang et al, 2018). However, as PAW is yet a novel technology, a detailed investigation of its mechanism of action and potential interactions with EPS matrix and other biofilm compounds is yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric air plasma damaged both the bacterial biofilm cells and its structural integrity. Scanning electron microscopy envinced the disruption of biofilms and pore formation in bacterial cells after exposure to plasma treatment [104]. The elevated reactive oxygen and nitrogen species in bacterial cells treated with atmospheric air plasma demonstrated their primary role in the observed bacterial inactivation process.…”
Section: Effects Of Cold Plasma Technology On Biofilm Formation On Fo...mentioning
confidence: 97%